PENGARUH BAHAN BAKAR PERTAMAX DENGAN CAMPURAN ETANOL 5%,10%,15% TERHADAP PRESTASI SEPEDA MOTOR 150 CC MANUAL - TAMBOS AUGUST SIANTURI (LP2MTBM MAKARIOZ, 2020)
Ethanol is an alternative energy especially for the fuel needs of the transportation equipment currently being developed. Theuse of ethanol has a positive impact on the side of fuel economy where the research aims to acquire the influence of theaddition of ethanol on the first fuel. Variations of the first fuel are; Mixture of first-etanol5% (E5), 10% (E10) and 15% (E15).Average torque obtained from dynotest results: Pertamax amounted to 13.6 Nm, a 5% first-ethanol (E5) mixture of 13.84Nm, 10% (E10) of 14.1 Nm, and 15% (E15) of 13.31 Nm. The average power obtained by the first was 7.31 kW, a first 5%(E5)-ethanol mixture of 7.47 kW, 10% (E10) of 7.48 kW, and 15% (E15) of 6.9 kW. The average specific fuel consumption(SFC) was obtained at a first of 172958.97 GR/kWh, the first mixture-ethanol 5% (E5) amounted to 165618.42 gr/kWh, 10%(E10) of 166688.92 GR/kWh, and 15% (E15) of 177567.45 GR/kWh. The average thermal efficiency obtained by Pertamaxwas 35.99%, first fuel-ethanol mixture of 5% (E5) of 38.40%, 10% (E10) of 42.42%, and 15% (E15) of 38.88%. (AFR) ratio ofthe average fuel air acquired first was 0.004435, the first fuel-ethanol mixture of 5% (E5) amounted to 0.004393; 10% (E10)of 0.004556; and 15% (E15) by 0.004595.